Gênero e justiça: a agência das mulheres na utilização de um serviço de justiça em São Leopoldo/RS - Azevedo, Victória Santos de (Universidade do Vale do Rio dos Sinos, 2021)
The present work concerns the theme of gender violence, specifically from the São Leopoldo Domestic Violence Court, in Rio Grande do Sul. I aim to understand the agency of women who use the services of the network to confront domestic violence and the functioning this network. Therefore, three spaces of the Court were observed: the courtroom, the corridor and, mainly, the waiting room, where a project coordinated by institutions that integrate the network takes place. Dialogue with the field of studies on gender violence in the social sciences and, specifically, using the concepts of agency, network and critical route. As a privileged methodology, I use ethnography, elaborated from participant observation, organized with the help of the construction of a field diary and informal conversations. The fieldwork was carried out from April 2019 to August 2019. Field research was an essential part of this research, since it was possible to build the understanding that the women's agency is directly crossed with other aspects such as issues of race and class, moreover, there was the possibility of observing that there are activisms that dynamize the network, bringing new possibilities for women.
Keywords: Gênero; Agência; Violência doméstica; Justiça; São Leopoldo/RS; Gender; Agency; Domestic violence; Justice; ACCNPQ::Ciências Humanas::Sociologia